HEPATOPROTECTIVE POTENTIALS OF ACTIVE FRACTIONS OF Lawsonia inermis (Lythraceae) AGAINST ACETAMINOPHEN-INDUCED LIVER DAMAGE IN RATS - NDATSU, YAKUBU; ABUBAKAR, HASSANA; BOKO USMAN, HAMZA; OLALEKAN ALIYU, AMUZAT; PAPA YISA, SOLOMAN (BIMA JOURNAL OF SCIENCE AND TECHNOLOGY GOMBE, 2022)
Lawsonia inermis (henna) is widely distributed across African countries. It has been used by herbal doctors in treating oxidative stress-related diseases in humans. Its leaves contain valuable antioxidants and protective molecules, which can protect humans against hepatic damage from toxic effects. This study analyzed the hepatoprotective ability of L. inermis leaf fractions against acetaminophen-induced liver damage in rats. Fifty-four (54) rats were divided into nine (9) groups, and each group allocated six (6) rats. Group 1, 2, 3, 4, 5, 6, 7, 8 and 9 were given 2 mL/kg/day of normal saline, normal control (NCN), 600 mg/kg/day of acetaminophen alone, negative control (NCA), 600mg/kg/day of acetaminophen and 200 mg of n-hexane fraction (AH200), 600mg/kg/day of acetaminophen and 400 mg of n-hexane fraction (AH400), 600 mg/kg/day of acetaminophen and 200 mg of ethyl acetate fraction (AE200), 600 mg/kg/day of acetaminophen and 400 mg of ethyl acetate fraction (AE400), 600mg/kg/day of acetaminophen and 200 mg of methanol fraction (AM200), 600mg/kg/day of acetaminophen and 400 mg of methanol fraction (AM400), 600mg/kg/day of acetaminophen and 25 mg/kg/day of silymarin (AS25), respectively. The serum chemistry, lipid profiles, hepatic enzyme markers and oxidative stress markers were analyzed using standard methods. Histopathological examination of hepatocytes of the treated rats was determined. The results revealed lower significant values of total protein, albumin, globulin, HDL, SOD, CAT, and GPx, and higher significant values of serum bilirubin, glucose, creatinine and urea, triglyceride, cholesterol, LDL, ALT, AST, ALP, LDH and MDA in NCA-treated rats than in the others. Interestingly, higher insignificantly levels of total protein, albumin, globulin, HDL, SOD, CAT, and GPx, and lowered insignificantly values of bilirubin, glucose, creatinine, urea, triglyceride, cholesterol, LDL, asnd ALT, AST, ALP, LDH, and MDA were noted among L. inermis fractions treated rats. Abnormal hepatic cell architectures were observed in the livers of NCA-treated rats than in other groups, however, reduced hepatic dysfunction/normal liver cell architectures were restored among the rats treated with L. inermis leave fractions. These results have suggested that all levels of L. inermis leave fractions in this study possessed hepatoprotective potential against acetaminophen-induced hepatic cell damage,